Knowledge Gaps in Mining Operations: Empirical Evidence from the Greek Lignite Mining Industry - Philip-Mark Spanidis; Francis Pavloudakis; Christos Roumpos (Materials Proceedings)
The objective of the paper is an introductory discussion on the knowledge gaps (KGs) observed in mining operations. A qualitative research (QLR) methodology, based on empirical evidence from the Greek mining industry, is discussed to identify the KGs appearing in mining operations and investigate the cause and criticality of each KG. Recommendations for the extension and integration of the methodology as a tool appropriate for introducing knowledge management (KM) in Greek mining organizations are provided.